Managerial influence on the diffusion of innovations within intra‐organizational networks. (30th July 2014) - Wunderlich, Philipp; Größler, Andreas; Zimmermann, Nicole; Vennix, Jac A. M.
Abstract This study analyzes the dynamics of intra‐organizational innovation implementation processes based on conversion within and migration between groups. We employ a diffusion model that extends often‐used epidemic models in three ways: (i) repeated acceptance and rejection decisions of adopters and non‐adopters; (ii) diffusion within and across groups organized in different network structures; and (iii) management's continuous influence on the diffusion process. The model is used to identify and evaluate senior management's possibilities to steer the diffusion process. Analyses reveal that network structure influences the interplay between the self‐reinforcing dynamics of conversion and the balancing dynamics of migration. Additionally, management can minimize diffusion time and invested resources by considering the proximity of groups to each other and to the network periphery. Providing structural explanations, this study offers insights into why, given various intra‐organizational networks, management policies can yield different results on whether and how innovations are adopted in an organization. Copyright © 2014 System Dynamics Society